2004
DOI: 10.1007/s00394-004-0474-2
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status remains critical in mother and infant in Central Anatolia (Kayseri) of Turkey

Abstract: Iodine deficiency with low urinary iodine excretion and high serum Tg and TSH concentrations were recognized among pregnant women and their babies in Kayseri in spite of the program of salt iodization. National measures are urgently required for improving the correction of iodine deficiency in Turkey. This includes regular supplementation with iodine, starting at preconception or in early pregnancy and continuing during the period of nursing in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 28 publications
2
37
0
9
Order By: Relevance
“…This may help explain why, in areas where there is an ID, BMIC is often greater than expected based on the UI concentration of lactating mothers 55,56 . The BMIC is strongly influenced by the mothers' iodine intake 58 .…”
Section: Iodine Intakes During Lactation and Urinary Iodine And Breasmentioning
confidence: 99%
See 1 more Smart Citation
“…This may help explain why, in areas where there is an ID, BMIC is often greater than expected based on the UI concentration of lactating mothers 55,56 . The BMIC is strongly influenced by the mothers' iodine intake 58 .…”
Section: Iodine Intakes During Lactation and Urinary Iodine And Breasmentioning
confidence: 99%
“…Most infants begin weaning by the second half of the first year of life, and some of the iodine requirement during that period will be met from weaning foods. Semba and Delange 58 proposed that a potential indicator of iodine status in a population could be the proportion of lactating women whose BMIC is $100 mg l 21 . Table 5 shows the BMICs of women living in areas where people are iodine sufficient or have mild-tosevere ID.…”
mentioning
confidence: 99%
“…Chanoine et al [11] found this to be 0.83 ml, Böhles et al [35] reported 0.76 ml in breastfed infants, Köksal et al [36] reported 0.82 ml and, in the study carried out by our institute in Kayseri and its districts among 70 mothers and newborns, the value was 0.79 ml [27]. …”
Section: Discussionmentioning
confidence: 99%
“…If, however, the average urine iodine value is between 5 and 9.9 μg/dl there is mild iodine deficiency. Values between 2 and 4.9 μg/dl constitute moderate deficiency, and values below 2 μg/dl represent severe iodine deficiency [15,27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Turkey has been long known as an area of mild to moderate iodine deficiency according to the figures obtained from previous epidemiological studies (Table 4). Kurtoglu et al [25] reported that in Central Anatolia (Kayseri) of Turkey, the mean thyroid volume of term newborns was 1.26 mL (SD ±0.36). After the national salt iodisation program, the same region of Kayseri reported that the mean thyroid volume was reduced to 0.99 mL (SD ±0.79).…”
Section: Discussionmentioning
confidence: 99%